2019
DOI: 10.1186/s12944-018-0949-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study showing no association between methylation levels of C3 gene promoter and the risk of CAD

Abstract: ObjectiveCoronary artery disease (CAD) is a multi-factor disease. Complement component 3 (C3) plays an important role in the development of CAD. The present study investigated the association between DNA methylation status of C3 gene promoter and the risk of CAD.MethodsOne hundred CAD patients and 1 hundred age-and gender- matched controls were recruited in current study. Methylation levels in CpG island in C3 promoter were determined by the method of bisulfite amplicon sequencing.ResultsMethylation levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a rat model of IRI, Pratt et al (206) found aberrant methylation in the C3 promoter gene in response to 24 h of cold ischemia and a subsequent 2 h of reperfusion, indicating an increased C3 release, therefore an amplification of local complement activation following the oxidative stress. However, these studies neither demonstrate a correlation between C3 aberrant methylation and increased gene expression (207) nor provided clinical translation data (208).…”
Section: Complement and Epigenetic Changes In Agingmentioning
confidence: 99%
“…In a rat model of IRI, Pratt et al (206) found aberrant methylation in the C3 promoter gene in response to 24 h of cold ischemia and a subsequent 2 h of reperfusion, indicating an increased C3 release, therefore an amplification of local complement activation following the oxidative stress. However, these studies neither demonstrate a correlation between C3 aberrant methylation and increased gene expression (207) nor provided clinical translation data (208).…”
Section: Complement and Epigenetic Changes In Agingmentioning
confidence: 99%